PENGARUH KUALITAS PRODUK, GAYA HIDUP DAN WORD OF MOUTH PADA KEPUTUSAN PEMBELIAN IPHONE DI BEKASI TIMUR - Ashraff Rizky Setyawan; Milda Handayani; Rini Wijayaningsih (IJESM Indonesian Journal of Economics and Strategic Management, 2025)
This study aims to analyze the influence of product quality, lifestyle and word of mouth on iPhone Purchasing Decisions. This study uses a quantitative method with an explanatory approach and a cross-sectional research design. The research sample consists of the number of respondents selected using the Accidental sampling technique. The research instrument is a questionnaire that has been tested for validity and reliability. Data analysis was carried out using the Partial Least Squares (PLS) method with the help of SmartPLS 3 software. The results of the study show that: 1) product quality has a significant effect on purchasing decisions, 2) lifestyle has a significant effect on purchasing decisions, 3) word of mouth has a significant effect on purchasing decisions